External beam boost versus interstitial high-dose-rate brachytherapy boost in the adjuvant radiotherapy following breast-conserving therapy in early-stage breast cancer: a dosimetric comparison - Terheyden, Martje Marie; Melchert, Corinna; Kovács, György (Journal of Contemporary Brachytherapy, 2016)
Purpose : This study aims to compare the dosimetric data of local tumor’s bed dose escalation (boost) with photon beams (external beam radiation therapy – EBRT) versus high-dose-rate interstitial brachytherapy (HDR-BT) after breast-conserving treatment in women with early-stage breast cancer. Material and methods : We analyzed the treatment planning data of 136 irradiated patients, treated between 2006 and 2013, who underwent breast-conserving surgery and adjuvant whole breast irradiation (WBI; 50.4 Gy) and boost (HDR-BT: 10 Gy in one fraction [n = 36]; EBRT: 10 Gy in five fractions [n = 100]). Organs at risk (OAR; heart, ipsilateral lung, skin, most exposed rib segment) were delineated. Dosimetric parameters were calculated with the aid of dose-volume histograms (DVH). A non-parametric test was performed to compare the two different boost forms. Results : There was no difference for left-sided cancers regarding the maximum dose to the heart (HDR-BT 29.8% vs. EBRT 29.95%, p = 0.34). The maximum doses to the other OAR were significantly lower for HDR-BT (Dmax lung 47.12% vs. 87.7%, p < 0.01; rib 61.17% vs. 98.5%, p < 0.01; skin 57.1% vs. 94.75%, p < 0.01; in the case of right-sided breast irradiation, dose of the heart 6.00% vs. 16.75%, p < 0.01). Conclusions : Compared to EBRT, local dose escalation with HDR-BT presented a significant dose reduction to the investigated OAR. Only left-sided irradiation showed no difference regarding the maximum dose to the heart. Reducing irradiation exposure to OAR could result in a reduction of long-term side effects. Therefore, from a dosimetric point of view, an interstitial boost complementary to WBI via EBRT seems to be more advantageous in the adjuvant radiotherapy of breast cancer.